Un-American: Latina high school students' testimonios of American and white conflation in the middle of nowhere. Issue 2 (4th March 2017) - Chang, Aurora
Abstract: Using a combination of counter-storytelling, testimonios, and Chicana feminist epistemology, I report on the findings of an ethnographic study that explores and analyzes the educational experiences of geographically isolated Latina high school students in a rural city in Wyoming. I demonstrate the labeling of these students by peers and teachers as 'Un-American' and the ways in which such a label is embedded in intersecting hegemonic discourses of whiteness, rurality and nationhood. It is through such labeling that white privilege is established and maintained and the immediate and future educational biographies of Latina/o students highly circumscribed.